Buffaloes: Promising Livestock for rural livelihood improvement - Dayal, Shanker (Indian Farming, 2018)
Buffalo is a triple purpose animal producing milk, meat and draught power. Buffalo contribute 53% of total milk production in India. It contributes 86% of total exported meat. Buffalo can efficiently utilize the roughages and crop byproducts into high quality milk suitable for a wide range of dairy products.